Perilaku Disfungsional Auditor Dalam Profesionalisme Akuntan - Ika Sasti Ferina; Ubaidillah; ana yulianita (Universitas Muhammadiyah Malang, 2023)
Purpose: The research objective was to measure and analyze the effect of professional skepticism, internal locus of control, external locus of control, professional commitment and profession ethics on auditor dysfunctional behavior at KAPs registered in the IAPI Directory for the South Sumatra Region. Methodology/approach: The data collection method uses a questionnaire technique with junior and senior auditor respondents who meet the sample criteria at the registered KAP. Data analysis used SEM PLS analysis technique. Findings: Based on the results of the analysis, it shows that Professional Skepticism, External Locus of Control, and Profession Ethics have a significant influence on Auditor Dysfunctional Behavior. Meanwhile, Internal Locus of Control and Professional Commitment do not have a significant effect on Auditor Dysfunctional Behavior. Practical implications: This research has practical implications for Public Accounting Firms, especially KAPs that are sampled in this study so that the results of this study can be used as material for consideration regarding factors that influence auditor dysfunctional behavior at work, both in the internal and external environment of the office. Originality/value: This study includes the variable professional commitment as an update in research on the topic of dysfunctional auditors.